The politics of air pollution : urban growth, ecological modernization, and symbolic inclusion - Gonzalez, George A., 1969- (SUNY series in global environmental policy., 2005)
"Who has been at the political forefront of clean air policy development in the United States? In The Politics of Air Pollution, George A. Gonzalez argues that the answer is neither the federal government, nor environmental groups, but rather locally oriented economic elites in conjunction with state and local governments. These local growth coalitions, composed of mostly large landholders, land developers, and the owners of regional media and utility firms, support clean air policies insofar as they contribute to the creation of a positive investment climate and, in turn, bring about greater profits through increased land values and an expanded local consumer base."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved